Implementasi Teknik Active Cycle Of Breathing (ACBT) Sebagai Asesmen Terhadap Dispnea pada Pasien Gagal Jantung - Candie Asteria, Bella; Nasrul Sani, Fakhrudin; Rosita, Ani; Dwi Kurniawan, Yanti (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Heart failure is a chronic and progressive condition in which the heart is unable to pump blood effectively, leading to clinical symptoms such as dyspnea, fatigue, pulmonary congestion, and reduced functional capacity. Dyspnea is one of the most prominent symptoms affecting patients’ quality of life and requires appropriate management. The Active Cycle of Breathing Technique (ACBT) is a non-pharmacological intervention designed to improve airway clearance, enhance lung expansion, and reduce breathing discomfort through structured breathing control, thoracic expansion exercises, and forced expiration techniques. This study aims to evaluate the implementation of ACBT as an assessment and therapeutic approach to reduce dyspnea in heart failure patients at RSUD dr. Darsono Pacitan. This case study used a descriptive pre–post test design involving two patients with heart failure experiencing dyspnea. ACBT was administered for three consecutive days, 1–2 sessions per day, with a duration of 10–15 minutes per session. Respiratory rate was measured before and after each intervention session. The findings show a decrease in respiratory rate in both patients, indicating reduced dyspnea after ACBT application. These results suggest that ACBT may serve as an effective non-pharmacological therapy to support respiratory function and reduce symptoms of dyspnea in heart failure patients.